ANALISIS FAKTOR RISIKO TERJADINYA PERDARAHAN POST PARTUM PADA IBU BERSALIN - Destri Lovandia; Titin Dewi Sartika Silaban; Sendy Pratiwi Ramadhani (Poltekkes Kemenkes Medan, 2022)
The World Health Organization estimates that about 810 women die every day from complications of pregnancy and childbirth. Maternal mortality rate (MMR) is the ratio of maternal mortality during pregnancy, childbirth, and postpartum caused by pregnancy, childbirth, and postpartum or their handling but not due to other causes. other causes such as accidental or incidental to every 100,000 live births. The maternal mortality rate is still high at 305 per 100,000 births. The causes of death that are often found in mothers are complications that occur during childbirth including 1,280 cases of bleeding, 1,066 cases of hypertension in pregnancy, and 207 cases of infection. Postpartum bleeding is bleeding vaginally 500 ccs or after the child is born. The purpose of this study was to determine parity, age, and spacing of pregnancies. This study uses an analytical survey method with a cross-sectional approach. The population used in this study were all mothers who gave birth, amounting to 958 people. The sampling technique of this research is simple random sampling by making the entire population a sample of 36 people. The results of the univariate analysis showed that 25 (69.4%) respondents had high parity and as many as 11 (30.6%), 17 (47.2%) respondents had a risk age and 19 (52.8%) and 16 (44, 4%) respondents have short birth spacing and as many as 20 (55.6%) respondents have normal birth spacing. From the results of the bivariate data analysis using the chi-square statistical test, it shows the limit of significance = 0.05, it is known that there is a significant relationship between parity p. value 0.004, there is a significant relationship between age p.value 0.008 and there is a significant relationship between gestational distance with the incidence of postpartum hemorrhage with p.value 0.003. Based on the results of this study, it is expected to be a contribution to advising health workers and the hospital to prevent the incidence of postpartum hemorrhage